Penanaman Karakter dalam Pembelajaran Bahasa Arab Daring pada Siswa Kelas VI MI DDI Tani Aman Loa Janan Ilir - Mustamin, Mustamin; Yamin, Muh.; Alina, Rafiqah (el Buhuth: Borneo Journal of Islamic Studies, 2019)
This research is based on the background of Internalizing (Instilling) Character Values ​​in Online Arabic Learning in Class VI MI DDI Tani Aman Loa Janan Ilir. The character education applied is quite embedded in the minds of students, this can be seen from the personality of the students of Madrasah Ibtidaiyah (MI) DDI Tani Aman which is considered good, the students are polite, devoted to their parents, respectful to those who are older, and helping each other. The objectives of this study are: 1) To find out how to instill character values ​​in online Arabic learning in class VI MI DDI Tani Aman Loa Janan Ilir. 2) What are the shortcomings and challenges faced by instilling character values ​​in online Arabic learning in class VI MI DDI Tani Aman Loa Janan Ilir. This research uses descriptive qualitative research. Sources of data in this study were Arabic Subject Teachers, Class VI MI-DDI Tani Aman students, and students' parents. Data collection techniques using observation, interviews and documentation. Meanwhile, the data analysis technique used is the Miles, Huberman and Saldana model, in three ways, namely data reduction/data reduction, data presentation/data display, and verification/verification. The validity of the data in this study using triangulation techniques. Internalization of character values ​​in learning Arabic online In class VI MI-DDI Tani Aman, it can be seen from the cultivation of nine indicator character values, namely the character of God's love and all of His creation, Independence and responsibility, Honesty/trust, diplomatic, Respectful and polite, Generous, likes to help and mutual cooperation/cooperation, Confident and hardworking, Leadership and justice, Kind and humble, Character of tolerance, peace, and unity. The drawbacks are in the method, syllabus, lesson plans, and networks when online, such as knowledge of existing technology / a little less understanding, lack of interaction between teachers and students so that children's lack of seriousness in learning, laziness in students and teachers rarely enter and The advantages are that the enthusiasm and hard work of the teachers and students are very good, many parents support or guide their children to learn especially Arabic lessons, the participation of parents in guiding and advising children at home so that they can create positive characters for children, as parents. really helped the formation of my child's character, memorization and the existence of a group made us work together.